Nutritional assessment of servicemen in relation to area of duty and feeding habits: a Pakistani prospective - Khan,M. A. F. (2023)
Abstract The present study was carried out to determine incidence of overweight and obesity in Pakistani servicemen with reference to their area of duty, feeding habits and also to identify risk factors. Accordingly, 2,501 servicemen selected from all over Pakistan using multiple stage stratified sampling protocol. Nutrition assessment performed using body mass index (BMI), waist to hip ratio (WHR) and dietary assessment using food frequency questionnaire. Collected data was analyzed using the SPSS version 25. Regression was used to find risk factors of obesity and WHR. Results indicated that about 1/4th of servicemen were smokers. Approximately, 1/5th of them were overweight and about one quarter were eating fruits and vegetables for <3 days/ week and <4 days/week, respectively. Only 1/3rd of them were physically active for at least <40 minutes per day. Age and fruits intake were significantly predicting BMI with a direct relation and vegetable intake was negatively correlated to BMI of the servicemen. Age and rank were significant predictors of WHR while, physical activity was negatively correlated to WHR. It is concluded and suggested from our study that there is a need to modify eating patterns and habits as well as improving physical activity on daily basis for healthy and long life of the servicemen.